[inaudible]: Point of Audition Representations of Deafness and the Cochlear Implant in A Quiet Place (2018). Issue 2 (1st December 2021) - BERRY, GABRIELLE
Abstract : Interrogating point of audition (POA) sound through the silences, noises, and closed captions of A Quiet Place 's critically lauded soundscapes, this article examines the ways point of audition aurally and rhetorically constructs deafness, technology, and the audio-viewer. In its sonic rendering of the post-apocalyptic world, A Quiet Place actively involves the audio-viewer in its fantastical conceit and 'fantasy' of deafness, folding the audience into the complex cyborgian politics and potential of the malfunctioning cochlear implant. This diegetic technological breakdown merges and tangles with the technology of the film, the point of audition sound highlighting the immersive capabilities and audist expectations of cinematic soundscapes. Yet, in this straining towards 'immersion', the uncaptioned silences of Regan's point of audition further accentuate issues of access, raising questions of the composition and meaning of immersion and silence. Through the shades of silence and sharp whining feedback of A Quiet Place, this article ultimately details the possibilities and complications of analysing point of audition sound, in the process, illustrating the harmonic resonation of the studies of sound, deafness, and disability. This article is the winner of the 2020 Claudia Gorbman Graduate Student Writing Award, selected by the Sound and Music Special Interest Group of the Society for Cinema and Media Studies in conjunction with Music, Sound, and the Moving Image.